Additive manufacturing of shape memory polymers: effects of print orientation and infill percentage on mechanical properties. Issue 4 (14th May 2018) - Villacres, Jorge; Nobes, David; Ayranci, Cagri
Abstract : Purpose: Material extrusion additive manufacturing, also known as fused deposition modeling, is a manufacturing technique in which objects are built by depositing molten materials layer-by-layer through a nozzle. The use and application of this technique has risen dramatically over the past decade. This paper aims to first, report on the production and characterization of a shape memory polymer material filament that was manufactured to print shape memory polymer objects using material extrusion additive manufacturing. Additionally, it aims to investigate and outline the effects of major printing parameters, such as print orientation and infill percentage, on the elastic and mechanical properties of printed shape memory polymer samples. Design/methodology/approach: Infill percentage was tested at three levels, 50, 75 and 100 per cent, while print orientation was tested at four different angles with respect to the longitudinal axis of the specimens at 0°, 30°, 60° and 90°. The properties examined were elastic modulus, ultimate tensile strength and maximum strain. Findings: Results showed that print angle and infill percentage do have a significant impact on the manufactured test samples. Originality/value: Findings can significantly influence the tailored design and manufacturing of smart structures using shape memory polymer and material extrusion additive manufacturing.